KOMPARASI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TIPE JIGSAW DALAM PEMBELAJARAN SEJARAH PADA SISWA KELAS XI SMA NEGERI 1 ANGKOLA BARAT - Salman Al Paris Sormin (Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to determine differences of historical learning outcomes with the application of cooperative learning type STAD and Jigsaw in learning history in Class XI SMA Negeri 1 Angkola Barat. Population in this research is class XI SMA Negeri 1 Angkola Barat. The sampling technique used in this study using cluster sampling technique is obtained class XI IPS as a sample of 64 people. Data analysis techniques used in this study is descriptive data analysis to see the state of variable research and statistical data analysis to test the research hypothesis by using t-test. Based on the results of research that has been done to get the picture that, the learning outcomes history using STAD type cooperative learning model obtained an average value of 75.37